Faktor-Faktor yang Berpengaruh Terhadap Audit Delay: Studi Meta Analisis: Studi Meta Analisis - Marisha Gabrila Sutanto; Carmel Meiden (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
The topic of factors that influence audit delay has been researched by many researchers and still exist until now. The existing research shows results that are consistent or inconsistent with different levels of significance. This study integrates various results from previous studies to test and generate conclusions regarding the factors that influence audit delay using the meta-analysis method. The data used was obtained through observation techniques in Publish or Perish software consisting of statistical results of research articles. The sample in this study are 18 research articles published in journals from 2012-2022 obtained from Google Scholar and selected by purposive sampling. The results of this study indicate that the independent variables of company size, profitability, audit opinion, and KAP size have an effect on audit delay. This study also proves that agency theory still applies to several manufacturing, banking, agricultural and mining companies in the 2012 to 2022 study period.